2019
DOI: 10.3390/cells8020145
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ Is a Transcriptional Regulator of Wee1 at the G2/M Phase of the Cell Cycle

Abstract: The CCAAT/enhancer-binding protein β (C/EBPβ) is a transcription factor that regulates cellular proliferation, differentiation, apoptosis and tumorigenesis. Although the pro-oncogenic roles of C/EBPβ have been implicated in various human cancers, how it contributes to tumorigenesis or tumor progression has not been determined. Immunohistochemistry with human non-small cell lung cancer (NSCLC) tissues revealed that higher levels of C/EBPβ protein were expressed compared to normal lung tissues. Knockdown of C/EB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…C/EBPβ is one transcription regulator involves in the cell cycle of G2/M [30] [35] demonstrated that knockdown C/EBPβ reduces in ammation, which is consistent with our present study. In ammationinduced miR-155 and inhibits the self-renewal of neural stem cells through suppressing the expression of C/EBPβ [36].…”
Section: Discussionsupporting
confidence: 93%
“…C/EBPβ is one transcription regulator involves in the cell cycle of G2/M [30] [35] demonstrated that knockdown C/EBPβ reduces in ammation, which is consistent with our present study. In ammationinduced miR-155 and inhibits the self-renewal of neural stem cells through suppressing the expression of C/EBPβ [36].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, we show that in presence of allele C in rs822336, PD-L1 transcription is regulated by the binding of both C/EBPβ and NFIC. In contrast, only C/EBPβ regulates PD-L1 transcription in presence of allele G. C/EBPβ is a TF that promotes the expression of many genes involved in several cellular processes such as apoptosis, cell differentiation, inflammation and tumorigenesis [ 81 , 82 ]. In contrast, NFIC is a TF involved in chromatin remodeling and epigenetic modulation by acting as activator or repressor of gene expression [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that XIST, miR-16-5p, WEE1 figure prominently in regulating the development and progression of NSCLC. 17,18,38,39 It is widely accepted that radiotherapy is currently one of the most effective methods for the treatment of a variety of advanced malignancies, including NSCLC. 2,40 However, the effect of radiotherapy is not satisfactory due to the reduced sensitivity of NSCLC cells to X-rays.…”
Section: Discussionmentioning
confidence: 99%